A Rare Cervical Dystonia Mimic in Adults: Congenital Muscular Torticollis (Fibromatosis colli), a Follow-up - Uluer, Mehmet C.; Bojovic, Branko (Frontiers in Neurology, 2016)
Neglected or undiagnosed congenital muscular torticollis (CMT) in adults is quite rare, although it is the third most common congenital deformity in the newborn [1]. When left untreated at an early age, deficits in lateral and rotational range of motion can occur along with irreversible facial and skeletal deformities that develop over time. Subtle cases can go unnoticed until early adulthood, with predominant fibrotic replacement in the sternocleidomastoid (SCM) making physical therapy and chemodenervation mostly ineffective. Surgical intervention, in these cases, can prove effective in alleviating pain, improving function and cosmesis [2]. We report an update on a previously reported case, misdiagnosed as cervical dystonia, which had undergone partial myectomy of the anterior belly of the SCM with some relief of symptoms but not total resolution after the correct diagnosis of fibromatosis colli [3].